Role of Cone Beam Computed Tomography in Rehabilitation of a Traumatised Deficient Maxillary Alveolar Ridge Using Symphyseal Block Graft Placement - Shipra Arora; Arundeep Kaur Lamba; Farrukh Faraz; Shruti Tandon; Abdul Ahad (Hindawi Limited, 2013)
Deficiencies in the alveolar ridges cause multiple problems in achieving aesthetic and functional outcome of implant therapy and are commonly restored by using onlay graft from intraoral source. Careful assessment of the recipient as well as the donor site using cone beam computed tomography (CBCT) is a prerequisite to ideal treatment planning. This paper highlights the critical role of CBCT in planning a successful rehabilitation of traumatised deficient anterior maxillary alveolar ridge using autogenous block graft from mandibular symphysis, followed by implant placement. A 21-year-old male reported with missing right maxillary lateral incisor due to traumatic avulsion 6 months back. A concavity was found on the labial aspect of edentulous area. Serial transplanar images on CBCT revealed gross irregular radiolucency in place of labial cortical plate. Using CBCT, size of the required block was estimated, and mandibular symphyseal area was evaluated for the feasibility of harvesting a graft of suitable dimension. Onlay block graft was harvested from mandibular symphysis and placed at the edentulous site to augment the alveolar ridge. Implants were placed 5 months later and loaded successfully after osseointegration. After 1 year of followup, implant-based prosthesis is working well, without any complications.